2016
DOI: 10.1111/1747-0080.12298
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes and behaviours of students enrolled in undergraduate nutrition and dietetics degrees

Abstract: These findings support previously expressed concern about presence of disordered eating in nutrition and dietetics undergraduates. Collaboratively developed support mechanisms for preventing and managing disordered relationships with food would be of benefit to students enrolled in nutrition degrees to ensure ongoing professional integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
6
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 34 publications
3
45
6
2
Order By: Relevance
“…This may instill habitual eating behaviours, which in later life increases the susceptibility to the cycles of restraint and binge-eating associated in some older populations with increased BMI [58]. Evidence to support this theory is provided by Rocks et al who studied undergraduate students and found that this group, with a similar age and background to our ≤25 years group, demonstrated high dissatisfaction with body weight and high rates of disordered eating behaviours [59]. An additional possibility is that BMI also mediates the effect of age on eating behaviours and food cravings.…”
Section: Discussionmentioning
confidence: 86%
“…This may instill habitual eating behaviours, which in later life increases the susceptibility to the cycles of restraint and binge-eating associated in some older populations with increased BMI [58]. Evidence to support this theory is provided by Rocks et al who studied undergraduate students and found that this group, with a similar age and background to our ≤25 years group, demonstrated high dissatisfaction with body weight and high rates of disordered eating behaviours [59]. An additional possibility is that BMI also mediates the effect of age on eating behaviours and food cravings.…”
Section: Discussionmentioning
confidence: 86%
“…The study is not without limitations, including a relatively low participation rate. Nutrition students may not be representative of the general population; however, this student population does not tend to differ in disordered eating attitudes and behaviors relative to other students (Rocks, Pelly, Slater, & Martin, 2017;Yu & Tan, 2016) and we observed mean scores on the EPSI comparable to or lower than other college samples (Forbush, Wildes, & Hunt, 2014;Kilwein, Goodman, Looby, & De Young, 2016). We also relied on self-reported BMI.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%